The Political Economy of Coastal Development - Pierre Magontier; Albert Solé-Ollé; Elisabet Viladecans Marsal (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the role of political parties as facilitators of intergovernmental cooperation regarding the development of coastal land. Slowing down this development has benefits (e.g., preservation of environmental amenities) and costs (e.g., job losses), not only for residents in the political jurisdiction but also for non-residents. Local governments may not consider the welfare of non-residents and therefore may not choose the right amount of development. This paper investigates how political alignment between mayors of nearby municipalities enhances the incentives to cooperate and affect development in coastal areas. We rely on high-quality administrative data from the cadaster on the amount of built-up land along the Spanish coast. Using a close-elections regression discontinuity design, we find that municipalities with mayors belonging to the ideological bloc governing a majority of municipalities in the coastal area develop less land than other municipalities. The effect is larger for land close to the coastline and in places with a large share of environmentally valuable land. This suggests that negative externalities are dominant in this context and that political parties are a useful tool to internalize them.
Keywords: D72; H70; R52; 330; local government; land use policy; regression discontinuity